'Nasi kandar': a study of eating habits and it's relations to a safe diet - Rahman, Abdul Rais Abdul (2012)
‘Nasi kandar’ was originated way back during the 18lh Century when Indian Muslim from Southern India migrated to Penang during the British Colonial period. It has evolve over the years is enjoyed by Malaysian from all walks of life regardless of age, gender, profession, race or religion thus becoming a multi-ethnic food. This outlet; factors that influence people to eat ‘nasi kandar’ and their eating habits; screen the microorganisms load in selected pairing dishes. A total of 122 Indian- Muslim stalls and restaurants in the Klang Valley and Penang were visited in order to compare food selection availability and locality. A total of 316 randomly selected patrons were picked up to answer a set of questionnaire concerning the reason for eating at the chosen food outlet and their typical choice of pairing dishes. Data from the questionnaires and observation list were analyzed with descriptive statistics using PASW 18.0 software. Thirty three random food samples were purchased and taken for lab testing to measure the existence of microorganisms specifically Staphylococcus aureus, Escherichia coli and coliforms. Rapid method using Petrifilm™ plates from 3M were used to count the bacteria loading instead of the conventional MPN method. More than half of the total respondent (58.9%) would consume ‘nasi kandar’ at least once a week while 41.1% consume more than once a week. Lunch time is the most popular time to eat ‘nasi kandar’. Chicken base dishes were the most diversed and widely available mainly for its cheaper price and have a more universal appeal to different race and religion thus making it the more popular choices among ‘nasi kandar’ partons. ‘Ayam go reng’ and ‘ikan go reng’ recorded S.aureus count of 4.4x102cfu/g and 1.3xl02 cfu/g respectively. Egg based samples showed a much higher count of E.coli, coliforms and S.aureus compared to meat based dishes, showing bacteria count ranging from 4.4xl02 cfu/g to 1.8xl04 cfu/g. Gravy base dishes in this study recorded of E.coli, Coliforms and S.aureus count ranging from below 1.5x10 cfu/g to 6.5x102 cfu/g. ‘Bendi’ recorded the highest E.coli (1.6xl03 cfu/g) and S.aureus (1.2xl03 cfu/g) counts. ‘Acar timun’ recorded the highest count for coliform bacteria (5.5x104 cfu/g). Bacteria are prone to thrive in vegetable and egg base items compare to gravies and fried items.